Hare e o Problema da Ladeira Escorregadia - Charles Feldhaus (Ethic@: an International Journal for Moral Philosophy)
This paper deals with Richard Hare's Kantian Utilitarianism aplied to bioethics and discusses his attempt to solve the problem of the slippery-slope. The distinction between two levels of moral thinking, the intuitive and the critical, is appointed by the philosopher as a possible solution. The question, then, is the following: can Hare really avoid the slippery-slope problem? The answer seems to be "no".